Study of Impact of Two way Fungibility on Realignment of Indian ADR Prices and their Underlying Domestic Prices - Kaur , Harpinder (Gyan Management Journal, 2008)
The Globalization of Indian capital markets has accelerated in the past decade.Increasing numbers of Indian firms have chosen to raise capital by issuing and listing their Depositary Receipts (DRs) in the oreign markets through ADR (US based ipstrument) and GD R European based instrument) .. This paper basically focuses on the relative pricing of stocks in segmented market i.e. in US markets through ADRs and their underlying shares in Indian stock market. It has been observed that Indian ADR prices have never almost equal to the prices of Indian share they represent, after correcting for exchange rate , hence it indicated lack of arbitrage opportunities. Earlier, only one way fungibilty was allowed - investors in ADRs /GDRs could convert their share into underlying domestic shares
Keywords: Study of Impact; Realignment of Indian; ADR Prices; Domestic Prices